Study Of Optimum Conditions For The Removal Of Ruthenium And Cerium Using Freshly Prepared Manganese Dioxide - AL- Taweel, Husam .H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The adsorption of Ru and Ce were carried out using manganese dioxide as adsorbent. The Optimization of the adsorption conditions were studied as a function of shaking time, nitric acid, metal ions, concentrations and temperature effects.      A rapid initial adsorption on MnO2 is followed by a steady and slow increase of metal uptake. The equilibration time is reached after four hours shaking for Ru and Ce and    the adsorption is much better from one molar acidic solution and 90Â°C.